Phenotypic and genetic spectrum of epilepsy with myoclonic atonic seizures. (29th May 2020) - Tang, Shan; Addis, Laura; Smith, Anna; Topp, Simon D.; Pendziwiat, Manuela; Mei, Davide; Parker, Alasdair; Agrawal, Shakti; Hughes, Elaine; Lascelles, Karine; Williams, Ruth E.; Fallon, Penny; et al.
Abstract: Objective: We aimed to describe the extent of neurodevelopmental impairments and identify the genetic etiologies in a large cohort of patients with epilepsy with myoclonic atonic seizures (MAE). Methods: We deeply phenotyped MAE patients for epilepsy features, intellectual disability, autism spectrum disorder, and attention‐deficit/hyperactivity disorder using standardized neuropsychological instruments. We performed exome analysis (whole exome sequencing) filtered on epilepsy and neuropsychiatric gene sets to identify genetic etiologies. Results: We analyzed 101 patients with MAE (70% male). The median age of seizure onset was 34 months (range = 6‐72 months). The main seizure types were myoclonic atonic or atonic in 100%, generalized tonic‐clonic in 72%, myoclonic in 69%, absence in 60%, and tonic seizures in 19% of patients. We observed intellectual disability in 62% of patients, with extremely low adaptive behavioral scores in 69%. In addition, 24% exhibited symptoms of autism and 37% exhibited attention‐deficit/hyperactivity symptoms. We discovered pathogenic variants in 12 (14%) of 85 patients, including five previously published patients. These were pathogenic genetic variants in SYNGAP1 (n = 3), KIAA2022 (n = 2), and SLC6A1 (n = 2), as well as KCNA2, SCN2A, STX1B, KCNB1, and MECP2 (n = 1 each). We also identified three new candidate genes, ASH1L, CHD4, and SMARCA2 in one patient each. Significance: MAE is associated with significant neurodevelopmental impairment. MAE is genetically heterogeneous, and we identified a pathogenic genetic etiology in 14% of this cohort by exome analysis. These findings suggest that MAE is a manifestation of several etiologies rather than a discrete syndromic entity.